Removal of inferior vena cava filter by open surgery after failure of endovenous retrieval - Tian, Xuan; Liu, Jianlong; Li, Jinyong; Jia, Wei; Jiang, Peng; Cheng, Zhiyuan; Zhang, Yunxin; Liu, Xiao; Zhou, M. I; Tian, Chenyang (Frontiers in Cardiovascular Medicine, 2023)
Background The permanent placement of inferior vena cava (IVC) filters may lead to numerous complications and their removal is recommended once the risk of pulmonary embolism is reduced. Removal of IVC filters by endovenous means is preferred. But failure of endovenous removal happens when recycling hooks penetrate the vein wall and filters are left in place for too long time. In these scenarios, open surgery may be effective for removal of IVC filters. We aimed to describe the surgical approach, outcomes, and 6-month follow-up of the removal of IVC filter by open surgery, after the failure of removal via the endovenous method. Methods A total of 1,285 patients with retrievable IVC filters were admitted from July 2019 to June 2021, including 1,176 (91.5%) endovenous filter removals, and 24 (1.9%) open surgical IVC filter removals after the failure by endovenous method, of whom 21 (1.6%) were followed-up and eligible for analysis of the study. Patient characteristics, filter type, filter removal rate, IVC patency rate, and complications were retrospectively analyzed. Results Twenty-one patients were left with IVC filters for 26 (10, 37) months, of which 17 (81.0%) patients had non-conical filters and 4 (19.0%) had conical filters; all 21 filters were successfully removed, with a 100% removal rate, no deaths, no serious complications, and no symptomatic pulmonary embolism. At the 3rd month follow-up after surgery and 3rd month follow-up after discontinuation of anticoagulation therapy, only 1 case (4.8%) had IVC occlusion, but without any occurrence of new lower limb deep venous thrombosis and silent pulmonary embolism. Conclusion Open surgery can be used for the removal of IVC filters after failure of removal by endovenous method or when accompanied by complications without symptoms of pulmonary embolism. Open surgical approach can be used as an adjunctive clinical intervention for the removal of such filters.